PENERAPAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SEKOLAH DASAR NEGERI 003 RENGAT - Yulita Yulita; Mahmud Alpusari; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Adstrac: The purpose of this research is to improve result of study IPS students of class IV SD Negeri 003 Rengat school year 2014 / 2015. The subject of this research are students of class IV SD Negeri 003 Rengat which consist of 21 students. Type of this research is collaborative action class research with two cycle. The data of research showing that result of students`study is increasing, the value of result of teacher activity on cycle I with average 62,5% . On cycle II increase with average 79,2% . students activities on cycle I with average 62,5% . and on cycle II increasing cooperative model type GI at based score which complete 6 students (28,57%) with average 53,52. Cycle I increase with complete attain 12 students (57,14%) with with average 74,28. Improving of all result of study 11,72% . based on this result can conclude that hypothesis in this research is “ if implementation of cooperative model type GI, so it can increasing result study IPS students of class IV SD Negeri 003 Rengat “ can acceptance.Keyword : Implementation of cooperative model type Investigation Group (GI), result of study IPS.